Incorporating Common-Cause Failures Into the Modular Hierarchical Systems Analysis - Liudong Xing; Shrestha, A.; Meshkat, L.; Wendai Wang (IEEE transactions on reliability, 2009)
This paper considers the problem of evaluating the reliability of hierarchical systems subject to common-cause failures (CCF); and dynamic failure behavior such as spares, functional dependence, priority dependence, and dependence caused by multi-phased operations. We present a separable solution that has low computational complexity, and which is easy to integrate into existing analytical methods. The resulting approach is applicable to Markov analyses, and combinatorial models for the modular analysis of the system reliability. We illustrate the approach, and the advantages of the proposed approach, through the detailed analyses of two examples of dynamic hierarchical systems subject to CCF.